Nutritional Status among Children with Cerebral Palsy attended at Medical University Hospital of Bangladesh (Journal of Current and Advance Medical Research, 2022)
Background: Feeding difficulty among children presented with cerebral palsy (CP) is a common problem which ultimately leads to malnutrition.Objective: The purpose of the present study was to assess the nutritional aspect in children with cerebral palsy.Methodology: This cross-sectional study was done in the Pediatric Neurology Unit of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. The children of cerebral palsy aged 1 to 10 years was enrolled in this study. Perinatal, developmental and feeding history was taken meticulously. Nutritional status was assessed by Welcome, Waterlow and WHO classification and on the basis of MUAC and BMI. Neurological assessment was done thoroughly and severity grading was done according to WHO manual 1987.Results: Majority (70.0%) of children were in the age group of 1 to 5 years. Most of the children were male (58.0%), born at term (90.0%) and had history of perinatal asphyxia (82.0%). Among enrolled children, 60.0% took adequate calorie. About 32.0% cases and 26.0% patient had difficulty in chewing and swallowing respectively whereas 54.0% faced drooling. Spastic quadriplegia (48.0%) was the most frequent type of Cerebral Palsy followed by mixed type (22.0%). According to Welcome classification, 32.0% cases had undernutrition and 6.0% cases had marasmus. Among children with marasmus, 66.7% cases had quadriplegia. Undernutrition was most frequent in quadriplegic and mixed type of cerebral palsy.Conclusion: Malnutrition is a common problem among patients with cerebral palsy. However severe malnutrition is less.Journal of Current and Advance Medical Research, January 2022;9(1):42-47